2020
DOI: 10.1177/0361684320939065
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Sense of Power, and Desire to Lead: Why Women Don’t “Lean In” to Apply to Leadership Groups That Are Majority-Male

Abstract: We investigated why women may have lower desires and intentions to apply to become a member of a leadership group (i.e., committee) than men when the majority of its members are men. In four studies, we examined the interaction between gender and gender composition of the leadership group on leader candidates’ sense of power, desire to lead, and intentions to apply to become a member of a leadership group. Informed by research on gender, perceived power, and the model of goal-directed behavior, we found that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The increase in the value ratings of power is the highest in the case of female BM students and the lowest in the case of male BM students. We know that women, compared to men, expect a lower sense of power when considering applying to a majority-male leadership committee (Goodwin et al , 2020). However, having entered a male-majority domain, there will be several occasions for the women to realize that they have to take charge and try to control people and resources if they were to survive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the value ratings of power is the highest in the case of female BM students and the lowest in the case of male BM students. We know that women, compared to men, expect a lower sense of power when considering applying to a majority-male leadership committee (Goodwin et al , 2020). However, having entered a male-majority domain, there will be several occasions for the women to realize that they have to take charge and try to control people and resources if they were to survive.…”
Section: Discussionmentioning
confidence: 99%
“…Tunç et al (2020) demonstrated that the value scores of female students for hedonism, universalism, benevolence and conformity were higher than those of male students, while the achievement scores were higher among male students. Goodwin et al (2020) found that women, compared to men, expected a lower sense of power when considering applying to a majority-male leadership committee. They also found that increasing women’s sense of power increased their desires and intentions to lead in a majority-male committee.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…According to Nishii ( 2013 ), to create more inclusive organizational environments, organizations must manage the problems and benefits associated with the various issues related to diversity. The technological area of ​​companies is generally a sector mostly composed of the male gender, which ends up reflecting in the discrepancy about the number of men and women members in the composition of the main committees existing in organizations, among them the HEIs – although there have been done some efforts to try to reduce this imbalance (Goodwin et al, 2020 ). Data obtained in this research corroborate this statement, for example: (i) the IT Steering Committee of Alpha is composed of only 25% female members, demonstrating that it is a committee formed, in its majority, by male professionals, and (ii) in the survey applied to the technology sectors of the 89 Brazilian educational institutions, 90.7% of respondents were men, reinforcing this discrepancy.…”
Section: Developing the It Governance Model Based On Dsr Guidelinesmentioning
confidence: 99%
“…Comparing with females, males are more likely to perceive themselves as having leadership traits and qualities (Eagly & Sczesny, 2009). Finally, females tend to report a lower sense of power (Carli, 2001;Goodwin et al, 2020;Steele, 1997;Wood & Rhodes, 1992). To reduce potential spurious results, gender (1=male; 0=female) was included as control variable.…”
Section: Control Variablementioning
confidence: 99%